PENERAPAN STRATEGI PEMBELAJARAN AKTIF SEPAK BOLA VERBAL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA MAN KAMPAR - Popilaya, Diana; Irianti, Mitri; Ma’aruf, Zuhdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to find out the improvement of the students motivation learning by applying strategy soccer verbal. This research is a this study is a pre-experiment One Group Pretest-Posttest Design. The subject of this research is students class XI at MAN Kampar , total of 37 students. The instrument of data gathering which used learning motivation of ARCS guestionaire, the techique of data extractionby bive pre questionaire and post questionnaire. Analyze data by description to see an increase in learning motivation. Based on data analyze the increase of learning motivation a in every indicator is increasing. Therefore learning motivation of class XI student of MAN Kampar on Theory of Kinetic Gas material having increased.Key Words: strategy soccer verbal, Motivation.